The Role of the Immune System in Huntington’s Disease - Gisa Ellrichmann; Christiane Reick; Carsten Saft; Ralf A. Linker (Clinical and Developmental Immunology)
Huntington’s disease (HD) is characterized by a progressive course of disease until death 15–20 years after the first symptoms occur and is caused by a mutation with expanded CAG repeats in the huntingtin (htt) protein. Mutant htt (mhtt) in the striatum is assumed to be the main reason for neurodegeneration. Knowledge about pathophysiology has rapidly improved discussing influences of excitotoxicity, mitochondrial damage, free radicals, and inflammatory mechanisms. Both innate and adaptive immune systems may play an important role in HD. Activation of microglia with expression of proinflammatory cytokines, impaired migration of macrophages, and deposition of complement factors in the striatum indicate an activation of the innate immune system. As part of the adaptive immune system, dendritic cells (DCs) prime T-cell responses secreting inflammatory mediators. In HD, DCs may contain mhtt which brings the adaptive immune system into the focus of interest. These data underline an increasing interest in the peripheral immune system for pathomechanisms of HD. It is still unclear if neuroinflammation is a reactive process or if there is an active influence on disease progression. Further understanding the influence of inflammation in HD using mouse models may open various avenues for promising therapeutic approaches aiming at slowing disease progression or forestalling onset of disease.